Alkaloid-based regimen is beneficial for acute myeloid leukemia resembling acute promyelocytic leukemia with NUP98/RARG fusion and RUNX1 mutation: A case report. Issue 40 (2nd October 2020) - Wei, Wei; Liu, Qiuju; Song, Fei; Cao, He; Liu, Mengmeng; Jiang, Yan; Li, Yanchun; Gao, Sujun
Abstract: Rationale: Some acute myeloid leukemia (AML) patients present with features mimicking the classical hypergranular subtype of acute promyelocytic leukemia (APL) but without the typical promyelocytic leukemia/retinoic acid receptor α (PML/RARα) rearrangement. Herein, we report an AML patient resembling APL but with nucleoporin 98/retinoid acid receptor gamma gene (NUP98/RARG) fusion transcript and Runt-related transcription factor 1 (RUNX1) mutation. Patient concerns: An 18-year-old male presented at the hospital with a diagnosis of AML. Diagnoses: The patient was diagnosed with bone marrow examination. Bone marrow smear displayed 90.5% promyelocytes. Fluorescence in situ hybridization analysis failed to detect the PML/RARα fusion transcript or RARα amplification. While real-time polymerase chain reaction showed positivity for the NUP98/RARG fusion transcript. G-banding karyotype analysis showed a normal karyotype. Interventions: The patient showed resistance to arsenic trioxide and standard 3 + 7 chemotherapy, but eventually achieved complete remission through the Homoharringtonine, Cytarabine, and Aclarubicin chemotherapy. Outcomes: These measures resulted in a rapid response and disease control. Lessons: Acute myeloid leukemia with the NUP98/RARG fusion gene and the RUNX1 mutation may be a special subtype of AML and may benefit from the alkaloid-based regimen.